2012
DOI: 10.1111/j.1574-6968.2012.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel family of bacterial dioxygenases that catalyse the hydroxylation of free l-amino acids

Abstract: l‐isoleucine‐4‐hydroxylase (IDO) is a recently discovered member of the Pfam family PF10014 (the former DUF 2257 family) of uncharacterized conserved bacterial proteins. To uncover the range of biochemical activities carried out by PF10014 members, eight in silico‐selected IDO homologues belonging to the PF10014 were cloned and expressed in Escherichia coli. l‐methionine, l‐leucine, l‐isoleucine and l‐threonine were found to be catalysed by the investigated enzymes, producing l‐methionine sulfoxide, 4‐hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Previously, we found that HilB from Pantoea ananatis AJ13355 also catalyzes the C‐4‐hydroxylation of l ‐isoleucine, but the K M value deduced from the kinetic analysis of this reaction was much greater than that determined for IDO, suggesting that l ‐isoleucine is not a natural substrate of HilB (Smirnov et al. ). In contrast to IDO, HilB is coexpressed with a putative dioxygenase, HilA.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Previously, we found that HilB from Pantoea ananatis AJ13355 also catalyzes the C‐4‐hydroxylation of l ‐isoleucine, but the K M value deduced from the kinetic analysis of this reaction was much greater than that determined for IDO, suggesting that l ‐isoleucine is not a natural substrate of HilB (Smirnov et al. ). In contrast to IDO, HilB is coexpressed with a putative dioxygenase, HilA.…”
Section: Introductionmentioning
confidence: 84%
“…l ‐leucine, l ‐isoleucine, and l ‐threonine were found to be hydroxylated by the PF10014 members, producing 4‐hydroxyleucine, 4‐hydroxyisoleucine, and 4‐hydroxythreonine, respectively (Smirnov et al. ). A detailed analysis of the genetic organization of PF10014 members revealed a unique operon structure (designated the Hil operon, from the h ydroxylation of i so l eucine) in the genomes of several gram‐negative plant pathogens belonging to the Pantoea and Pseudomonas genera (Smirnov et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations